청소년의 정서성과 정서조절전략 및 자기통제력 - 한선화(Sun Hwa Han); 현온강(On Kang Hyun) (Korean Journal of child studies, 2006)
Analysis of the data concerning 525 middle and high school students showed that positive affect correlated positively with cognitive reappraisal strategy and with self-control but correlated negatively with expressive suppression strategy. Negative affect correlated positively with expressive suppression strategy and negatively with self-control. The group of higher positive and higher negative affect was higher than the group of lower positive and lower negative affect in cognitive reappraisal strategy. The group of higher positive and higher negative affect was higher than the group of higher positive and lower negative affect in expressive suppression strategy. The group of higher positive and lower negative affect was higher than the group of higher positive and higher negative affect in self-control.